Complex formation of chlorhexidine gluconate with hydroxypropyl-β- cyclodextrin (HPβCD) by proton nuclear magnetic resonance spectroscopy (1H NMR) - Onnainty, Renée (2011)
The complex formation of chlorhexidine digluconate (CHX-G2) with hydroxypropyl-β-cyclodextrin (HPβCD) was studied using NMR spectroscopy. The results revealed that this surfactant agent shows an monomer/aggregate equilibrium, which is dependent on the concentration of this drug. This equilibrium can be modified by the presence of HPβCD, which reduces the aggregation of the CHX-G2 molecules. An inclusion process of the CHX-G2 aromatic residue within the cyclodextrin cavity was confirmed by 2D ROESY spectroscopy. 1H NMR titration studies of CHX-G2 with HPβCD in D2O confirmed the formation of higher order complexes between CHX-G2 and HPβCD. Moreover, the addition of HPβCD into CHX-G2 solutions forms insoluble aggregates. Such insoluble aggregates may result in the stacking of CHX-G 2 molecules on the surface of the CHX-G2:HPβCD complexes.